SISTEM INFORMASI MANAJEMEN PELAYANAN PADA KLINIK PRATAMA DENGAN METODE CRM - Intan Oktaviani; Khoirul Mustofa; Sarwendah Maragawati (Jurnal Elektronika Listrik dan Teknologi Informasi Terapan, 2020)
Information systems become the main thing in a company, in terms of supporting the development of the business. Information systems can facilitate the performance of a business entity. With the existence of an information system, it is expected that a business can be more optimal in managing business reporting both needed by internal and external parties. To be able to provide effective and efficient services, computer-based services that need to be done. The method used in making this application is the Prototyping method with this method is a method for building a software that is not too large and human resources involved in a limited amount. The steps taken are planning, analysis, system design, implementation. The purpose of making this application is to facilitate patients in the service of information and examinations. As well as saving addresses and energy by building this prototype system. There is also a strategy developed in the form of customer relationship management (CRM) is a strategy used by companies to manage interactions with customers and potential customers. CRM helps organizations streamline processes, build customer relationships, increase sales, improve customer service, and increase profitability. The results of the research found in making proptotypes at the Sri Panimbing Klaten Clinic are able to provide information that can be accessed anywhere and at any time as well as online reservation services that make it easy for patients, doctors, and administrators to conduct the queue process.